The Importance Of Physical Activity And Community Participation Amongst Women For A Better Quality Of Life: A Cross-Sectional Study of Indonesia Family Life Survey - Faiza Yuniati; Sherli Shobur; Intan Kumalasari; Lukman; Devi Mediarti; Rizki Sri Haryanti (International Journal of Health Engineering and Technology, 2022)
Background:The quality of life differs according to individual characteristics and social life. Employment status impacts women's role in family and society. Income influences many aspects of women's lives. This research was designed to compare the quality of life of employed women with unemployed womens. This study is quantitative research in public health to determine the quality of  life of employed women and unemployed womens. This study used data from the Indonesia Family Life Survey in 2014. The first (IFLS1) wave was conducted in 1993–1994. The survey individuals represented almost 83% of the Indonesian population residing in 13 of the country’s 26 provinces. IFLS5 was carried out in 2014-2015 and the individual re-contact rate was 90.5%. The number of women in the 2014 IFLS data aged 22-55 years who were not attending school is 10,661. Subjects with complete data in this study were 7169. Primary activities during the past week such as being employed and homemakers were eligible criteria. The average QoL score of employed women was higher than unemployed womens, with the mean difference was 0.019. The person correlation reveals no differences in overall QoL for both groups. Despite the Pearson correlation test revealing no significant difference in overall quality of life, employed women rated higher scores for almost dimensions of quality of life (well-being, general health, physical activity, social participation, religion, and social environment). The current study identified significant differences in physical activity and community participation for the two groups. The quality of life of employed women is better than unemployed. This study provides the ensuing practical implications regarding regular physical activity and getting involved in community programs. It is necessary to strengthen the support system. Furthermore, health promotion is essential for women to take responsibility for chores and achieve social support by engaging in community activities.